Aerobic Metabolism of 4-Hydroxybenzoic Acid in Archaea via an Unusual Pathway Involving an Intramolecular Migration (NIH Shift) - Fairley, D. J. (American Society for Microbiology, 2002)
A novel haloarchaeal strain, Haloarcula sp. strain D1, grew aerobically on 4-hydroxybenzoic acid (4HBA) as a sole carbon and energy source and is the first member of the domain Archaea reported to do so. Unusually, D1 metabolized 4HBA via gentisic acid rather than via protocatechuic acid, hydroquinone, or catechol. Gentisate was detected in 4HBA-grown cultures, and gentisate 1,2-dioxygenase activity was induced in 4HBA-grown cells. Stoichiometric accumulation of gentisate from 4HBA was demonstrated in 4HBA-grown cell suspensions containing 2,2′-dipyridyl (which strongly inhibits gentisate 1,2-dioxygenase). To establish whether initial 1-hydroxylation of 4HBA with concomitant 1,2-carboxyl group migration to yield gentisate occurred, 2,6-dideutero-4HBA was synthesized and used as a substrate. Deuterated gentisate was recovered from cell suspensions and identified as 3-deutero-gentisate, using gas chromatography-mass spectrometry and proton nuclear magnetic resonance spectroscopy. This structural isomer would be expected only if a 1,2-carboxyl group migration had taken place, and it provides compelling evidence that the 4HBA pathway in Haloarcula sp. strain D1 involves a hydroxylation-induced intramolecular migration. To our knowledge, this is the first report of a pathway which involves such a transformation (called an NIH shift) in the domain Archaea.